PENJATUHAN PIDANA PENJARA TERHADAP TERDAKWA ANAK DALAM PERKARA PENCABULAN (STUDI PUTUSAN NOMOR 6/PID.SUS-ANAK/2022/PN WNG) - Saputri, Anisa Septiana; Santoso, Bambang (Verstek, 2023)
This study aims to determine the appropriateness of the judge's considerations in imposing prison sentences on child defendants in cases of obscenity in the Wonogiri District Court Decision Number 6/Pid.Sus-Anak/2022/PN Wng with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The research methodology uses normative legal research and a case approach technique, as well as library research legal material collection techniques to obtain laws related to the problem under study. The results of this study are that imprisonment can only be imposed on children for a maximum of 1/2 (one half) of the sentence for adults. In addition, the provisions of Article 82 Paragraph (4) of Law Number 17 of 2016 concerning Child Protection with an additional sentence of 1/3 (one third) of the criminal threat cannot be applied. To children, even though the child's actions have been proven to fulfill the elements of the paragraph, the additional punishment is excluded for child offenders.Keywords: Child; Obscenity; Prison; Judge's Decision